From Poverty to Inequality: Evaluation of the Implementation of the Family Hope Program (PKH) and its Impact on Social Inequality in North Sumatra - Ulandari, Sri Ayu; Sampurna, Ahmad (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to evaluate the implementation of the Family Hope Program (PKH) in Sei Lumut Village, North Sumatra Province, with a focus on its impact on community welfare, obstacles faced in program implementation, and social inequality that arises among the community. In addition, this study also aims to identify strategies that can be used to optimize the effectiveness of the PKH program in reducing social inequality in the village. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The research findings show that the social inequality that is created is not only caused by miscommunication, but also by the lack of mechanisms that allow for adjustments to the socio-economic status of recipients of the Family Hope Program assistance. Irregular data updates exacerbate this gap, while unclear communication causes confusion among beneficiaries. This study contributes to understanding how better data management and communication can improve the effectiveness of PKH and reduce social inequality in the community. Therefore, aid management must improve the data management system and strengthen coordination between stakeholders, as well as improve socialization to aid recipients to be more effective